Pengaruh Social Media Advertising dan Kualitas Pelayanan Terhadap Loyalitas Melalui Kepuasan Pelanggan Sebagai Variabel Intervening: Studi Kasus Devi Salon Medan - Suci Arifah Lubis; Tuti Anggraini; Muhammad Ikhsan Harahap (STIKes Ibnu Sina Ajibarang, 2024)
This research aims to determine the influence of Social Media Advertising and Service Quality on Loyalty through Customer Satisfaction as an Intervening variable (Case Study of Devi Salon Medan). This research uses a quantitative approach with data collection using the Likert scale method. The subjects used in this research were 100 Devi Salon Medan customers and were taken using purposive sampling. The data analysis technique uses SPSS version 23. The results of this research show that overall each partial test states that it has a significant and positive effect between the variables. Where the statistical results state that the α value is <0.05. The Path analysis test also shows that there is a direct influence and an indirect influence on each variable which is connected through variable Z. And it also simultaneously shows that there is an influence of Social Media Advertising and Service Quality which together have an influence on Loyalty through the Customer Satisfaction variable.